Faktor sosial ekonomi dengan Kejadian anemia pada remaja putri - Mahda Rizka; Rilyani Rilyani; Aryanti Wardiyah (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI), 2024)
Abstract Background: Anemia is a common problem among teenagers, especially young women. The cause is poor diet which has an impact on the nutritional status of the younger generation. Normal Hb levels in adolescent girls are (>12 g/dl). The incidence of anemia in adolescent girls is 29%. One of the factors causing anemia is socio-economic factors. Purpose: To determine the comparison of anemia with socioeconomic factors in adolescent girls at SMAN 7 and SMAN 14 in Kemiling, Bandar Lampung in 2024. Method: This is a quantitative study using a cross-sectional approach. The population consisted of adolescent girls from SMAN 7 and SMAN 14, totaling 261 respondents. The sampling technique used was random sampling. Results: In SMAN 14, 14.1% of students have abnormal menstrual periods and 85.9% have normal periods. In SMAN 7, 21.4% have abnormal menstrual periods and 78.6% have normal periods. In SMAN 14, 59.2% are anemic and 40.8% are non-anemic. In SMAN 7, 48.6% are anemic and 51.4% are non-anemic. In SMAN 14, 8.4% of parents have low education and 91.6% have high education; 22% of parents are unemployed and 78% are employed; 67.5% of parents have low income and 32.5% have high income. In SMAN 7, 7.1% of parents have low education and 92.9% have high education; 1.4% of parents are unemployed and 98.6% are employed; 65.7% of parents have low income and 34.3% have high income. Conclusion: In SMAN 14, out of 191 respondents, 113 (59.2%) are anemic, 175 (91.6%) have high parental education, 149 (78%) have employed parents, and 129 (67.5%) have low parental income. Low economic status leads to nutritional limitations for children. Pendahuluan: Anemia merupakan masalah yang umum terjadi di kalangan remaja, khususnya remaja putri. Penyebabnya adalah pola makan yang buruk sehingga berdampak pada status gizi generasi muda. Kadar Hb normal pada remaja putri adalah (>12 g/dl) Kejadian anemia pada remaja putri adalah 29%. Salah satu faktor penyebab anemia adalah faktor sosial ekonomi. Tujuan: Untuk diketahuinya perbandingan Anemia dengan Faktor sosial ekonomi pada remaja putri di SMAN 7 dan SMAN 14 di Kemiling Bandar Lampung tahun 2024. Jenis penelitian yang di gunakan kuantitatif. Metode: Menggunakan pendekatan cross sectional. Populasinya adalah remaja putri di SMAN 7 dan SMAN 14 sejumlah 261 responden. Teknik sampling yang di gunakan random sampling. Hasil: Lama menstruasi di SMAN 14 sebanyak 14.1% tidak normal dan 85.9% normal. Sedangkan di SMAN 7 lama menstruasi 21.4% tidak normal dan 78.6% normal. Anemia di SMAN 14 sebanyak 59,2% anemia dan 40,8% tidak anemia. Sedangkan di SMAN 7 sebanyak 48.6% anemia dan 51,4% tidak anemia. Di SMAN 14 pendidikan orang tua 8,4% rendah dan 91.6% tinggi, pekerjaan orang tua 22% tidak bekerja dan 78% bekerja, pendapatan orang tua 67.5% rendah dan 32.5% tinggi. Sedangkan di SMAN 7 pendidikan orang tua 7.1% rendah dan 92.9% tinggi, pekerjaan orang tua 1.4% tidak bekerja dan 98.6% bekerja, pendapatan orang tua 65.7% rendah dan 34.3% tinggi. Simpulan: Di SMAN 14 anemia 113 responden (59.2%), pendidikan orang yang tinggi 175 responden (91.6%), pekerjaan orang tua yang bekerja 149 responden (78%), pendapatan orang tua yang rendah 129 responden (67.5%). Karena ekonomi yang rendah menyebabkan anak mengalami keterbatasan untuk mendapatkan gizi yang seharusnya.